TRAVEL BEHAVIOR AND RESPONSES TO CHANGE IN TRANSIT FARE: A COMPARATIVE STUDY OF URBAN RAIL PASSENGERS BETWEEN BANGKOK AND MANILA - Marcus Kyle Taracatac Baron (Chulalongkorn University, 2014)
115 pages